Pengembangan Model Pembelajaran Berbasis Masalah Berbantuan Concept Mapping Pada Keterampilan Menulis Teks Eksposisi Analitis - Zaghu, Yeni Pala; Kuswandi, Dedi; Wedi, Agus (JKTP: Jurnal Kajian Teknologi Pendidikan, 2023)
This research aims to produce a product in the form of the syntax of a problem-based learning model assisted by concept mapping on analytical exposition text. The method used in this research uses the Dick and Carey development model. Data were obtained through the product validation process by design experts and material experts, then small group trials and large group trials were conducted with eleventh-grade natural science students at St. Thomas Aquinas Sumba High School. The results of validation by learning design experts and material experts obtained that the learning model developed is suitable for use in the learning process. The results of the small group trial obtained data from learner responses that the learning model developed was practical and interesting. Meanwhile, to see the effectiveness of the learning model developed, data was collected from pretest and posttest, then paired sample t-test was conducted. The result shows that the problem-based learning model assisted by concept mapping is effective in the learning process.AbstrakPenelitian ini bertujuan untuk menghasilkan sebuah produk berupa sintaks dari desain model pembelajaran berbasis masalah berbantuan concept mapping yang bisa digunakan dalam proses pembelajaran. Desain model pembelajaran ini diuji cobakan pada mata pelajaran Bahasa inggris pada materi eksposisi analitis. Pengembangan model desain pembelajaran ini mengikuti model pengembanagan Dick and Carey. Produk yang dihasilkan ini sebelum di uji cobakan pada peserta didik dilakukan uji validasi oleh ahli desain pembelajaran dan ahli materi. Uji coba pemanfaatan desain model pembelajaran ini diuji cobakan pada peserta didik kelas XI IPA1 dan XI IPA2. Hasilnya menunjukkan bahwa desain model pembelajaran layak,praktis dan menarik serta efektif. Sehingga dapat disimpulkan bahwa perlunya pengembangan desain model pembelajaran pada keterampilan menulis Bahasa inggris.